Pengaruh Media Pembelajaran Aplikasi Whatsapp Terhadap Minat dan Hasil Belajar Peserta Didik - Muh Iqbal Jufri; Hasnawi Haris; Rifdan Rifdan (Phinisi Integration Review, 2022)
This study aims to determine the effect of the WhatsApp application learning media on students' learning interest in Civics lessons in distance learning at SMP Negeri 2 Palopo, and to determine the effect of WhatsApp application learning media on student learning outcomes in Civics lessons in distance learning at State Junior High Schools. 2 Palopo. This type of research uses ex-post facto research, taking a sample of 161 students who were selected randomly with probability sampling technique. There are two data analysis techniques used in this study, namely, descriptive statistical analysis and inferential statistical analysis. The data collection techniques used were questionnaires, learning outcomes data and documentation. The results showed that (1) WhatsApp application learning media had a significant influence on participants' learning interest. students in Civics lessons in distance learning at SMP Negeri 2 Palopo. This can be seen from the results of data processing using Statistical product and service solution (SPSS) 22 R value 0.575 and tcount 8.864 > ttable 1.654 with a significance of 0.000 <0.05 which means H1 is accepted in other words the learning media has a positive and significant influence on learning interest of students in Civics lessons. (2) WhatsApp application learning media has a significant effect on student learning outcomes in Civics lessons in distance learning at SMP Negeri 2 Palopo. This can be seen from the results of data processing using Statistical product and service solution (SPSS) 22 R value 0.406 and tcount 5.596 > t table 1.654 with a significance of 0.000 <0.05 which means H1 is accepted in other words the learning media has a positive and significant effect on learning outcomes students in PPKn lessons. Penelitian ini bertujuan untuk mengetahui pengaruh media pembelajaran aplikasi WhatsApp terhadap minat belajar peserta didik pada pelajaran PPKn dalam pembelajaran jarak jauh di SMP Negeri 2 Palopo, dan mengetahui pengaruh media pembelajaran aplikasi WhatsApp terhadap hasil belajar peserta didik pada pelajaran PPKn dalam pembelajaran jarak jauh di SMP Negeri 2 Palopo.Jenis penelitian inimenggunakan penelitian ex-post facto, pengambilan sampelberjumlah 161 peserta didik yang dipilih secara random dengan teknik probility sampling. Teknik analisis data yang digunakan penelitian ada dua yaitu, analisis Statistika Deskriptif dan analisis Statistika Inferensial.Teknik pengumpulan data yang digunakan yaitu angket, data hasil belajar dan dokumentasi.Hasil penelitian menunjukkan bahwa (1)  Media pembelajaran aplikasi WhatsApp memiliki pengaruh signifikan terhadap minat belajar peserta didik pada pelajaran PPKn dalam pembelajaran jarak jauh di SMP Negeri 2 Palopo. Hal ini dapat dilihat dari hasil pengelolahan data mengunakan Statistical product and service solution (SPSS) 22 nilai R 0,575 dan nilai thitung 8,864 > ttabel 1,654 dengan signifikansi 0,000 < 0,05 yang artinya H1 diterima dengan kata lain media pembelajaran memiliki pengaruh positif dan signifikan terhadap minat belajar peserta didik pada pelajaran PPKn. (2) Media pembelajaran Aplikasi WhatsApp memiliki pengaruh Signifikan terhadap hasil belajar pesertadidik pada pelajaran PPKn dalam pembelajaran jarak jauh di SMP Negeri 2 Palopo. Hal ini dapat dilihat dari hasil pengelolahan data mengunakan Statistical product and service solution (SPSS) 22 nilai R 0,406 dan nilai thitung 5,596 >ttabel 1,654 dengan signifikansi 0,000 < 0,05 yang artinya H1 diterimadengan kata lain media pembelajaran berpengaruh positif dan Signifikan terhadap hasil belajar pesertadidik pada pelajaran PPKn.